2023
DOI: 10.1021/acs.chemmater.2c03151
|View full text |Cite
|
Sign up to set email alerts
|

Phase Competition and Strong SHG Responses of the Li2MIIMIVSe4 Family: Atom Response Theory Predictions versus Experimental Results

Abstract: Compounds of diamond-like (DL) structures are one of the important systems in searching for new high-performance infrared nonlinear optical (IR NLO) materials. However, the phase competition of the diverse DL allotropes and the origin of the SHG response at the atom and orbital level for these NLO materials remain an unsolved hot topic. In this work, the atom response theory (ART) combined with the hybrid density functional calculations was applied to explore the NLO properties of the Li2 M II M IVSe4 (M II = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The interatomic distance exists b/w the family of IV and V group atoms, remains practically same with the replacement of II group atoms. 52 In case of dopant effect on the pristine system, we observed that the bulk modulus decreases with increasing (Sb, Bi and Ba) atom concentrations. In this investigation, (E) is fitted as a main function of volume (V) chosen form the 3rd order Birch-Murnaghan's relations 53 of state is given by ( ) Where, E f is called formation energy, E T denoted the total energy and E , Zn E , Si E , Sb E P and E Ba represents the solid energies of Zn, Sb, Ba, Si and P atoms respectively.…”
Section: Computational Methodologymentioning
confidence: 72%
See 1 more Smart Citation
“…The interatomic distance exists b/w the family of IV and V group atoms, remains practically same with the replacement of II group atoms. 52 In case of dopant effect on the pristine system, we observed that the bulk modulus decreases with increasing (Sb, Bi and Ba) atom concentrations. In this investigation, (E) is fitted as a main function of volume (V) chosen form the 3rd order Birch-Murnaghan's relations 53 of state is given by ( ) Where, E f is called formation energy, E T denoted the total energy and E , Zn E , Si E , Sb E P and E Ba represents the solid energies of Zn, Sb, Ba, Si and P atoms respectively.…”
Section: Computational Methodologymentioning
confidence: 72%
“…After discussions of single and codoping effect, we computed the Phonon dispersion relation and PDOS for multiple (Sb, Bi and Ba) doping effect on pristine system. Current computation of phonon curves in linear responses technique under the main frame of density functional perturbation (DFTP) 52. In this case electron ion interaction as well as exchange correlation functions exist were used under the norm conserving (NCPP) and (GGA+PBE) respectively.…”
mentioning
confidence: 99%
“…Solid-state lasers that operate in the mid-infrared range have important applications such as noninvasive surgery, environmental monitoring, and military equipment . The frequency conversion processes occurring in these lasers rely on nonoxide nonlinear optical (NLO) crystals. Many IR NLO materials, including those that are most commonly encountered in commercial use (e.g., AgGaS 2 , AgGaSe 2 , and ZnGeP 2 ), are derived from chalcopyrite and related structures, generally referred to as diamond-like semiconductors. Their performance depends on many competing factors that must be balanced, foremost among which are a strong second harmonic generation (SHG) response and a high laser-induced damage threshold. Herculean efforts have been expended to evaluate other candidates, often predicated on enthusiastic claims of rational design, but to date, none have really threatened to displace the few existing commercial materials.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the fundamental building block [MQ 4 ] tetrahedron (M = metal cations; Q = S, Se, Te) in the DL structure is always arranged in an aligned manner, which will lead to the superposition of the microscopic second-order susceptibility, resulting in a larger SHG response . For decades, plentiful chalcogenides with a DL structure have been reported, mainly including the I–III–Q 2 (I = Li, Ag; III = Al, Ga, In; Q = S, Se, Te) family, ,, I 2 –IV–Q 3 (I = Ag, Cu; IV = Si, Ge, Sn; Q = S, Se) family, I 3 –V–Q 4 (I = Li, Ag, Cu; V = P, As, Sb; Q = S, Se) family, I 2 –II–IV–Q 4 (I = Li, Ag, Cu; II = Zn, Cd, Hg; IV = Si, Ge, Sn; Q = S, Se) family, and I 4 –II–IV 2 –Q 7 (I = Li, Ag; II = Zn, Cd, Hg, Mn; IV = Si, Ge, Sn; Q = S, Se) family. , However, most of the compounds mentioned above are sulfides and selenides, and tellurides with DL structures are rarely reported. Compared with sulfides and selenides, tellurides generally possess a larger electronic polarization and a wider transmittance range, making them potentially more suitable candidates as MFIR NLO materials …”
Section: Introductionmentioning
confidence: 99%